The Influence of Marketing Strategy and Service Effectiveness on Consumer Satisfaction at Lotte Grosir Medan - Yohana Melita Silalahi; Atika Aini Nasution; Zahara Meutia (International Forum of Researchers and Lecturers, 2024)
This study aims to analyze the influence of Marketing Strategy and Service Effectiveness on Customer Satisfaction at Lotte Grosir Medan. A quantitative approach was used, with data collected through a survey distributed to 100 consumers who participated as respondents. The variables examined include Marketing Strategy (X1), Service Effectiveness (X2), and Customer Satisfaction (Y), measured using a 5-point Likert scale and analyzed with the Statistical Package for the Social Sciences 29 (SPSS 29). The results indicate that the Marketing Strategy is rated as satisfactory with an average score of 3.88, while Service Effectiveness also falls within the satisfactory category with an average score of 3.97. Overall, Customer Satisfaction reached an average score of 3.93, which is also categorized as satisfactory. Regression analysis proves that Marketing Strategy has a positive and significant effect on customer satisfaction, with a positive value of 0.575, t-count of 12.207 > t-table 1.988, and significance of 0.001 < 0.05. Service Effectiveness also positively and significantly influences Customer Satisfaction, with a positive value of 0.365, t-count of 8.020 > t-table 1.988, and significance of 0.001 < 0.05. Together, the variables Marketing Strategy and Service Effectiveness have a positive and significant effect on Customer Satisfaction, with an F-count of 1406.788 > F-table 3.09 and a significance of 0.001 < 0.05. The better the marketing strategy and services implemented by Lotte Grosir Medan, the higher the level of customer satisfaction achieved.